Population genetic structure and temporal stability among Trypanosoma brucei rhodesiense isolates in Uganda - Kato, Charles D.; Alibu, Vincent P.; Nanteza, Ann; Mugasa, Claire M.; Matovu, Enock (Parasites & Vectors, 2016)
The population structure and role of genetic exchange in African trypanosomes have been previously analyzed albeit with contradictory findings. To further investigate the role of genetic polymorphism on the population genetic structure of Trypanosoma b. rhodesiense, we hypothesized that parasite genotypes are clonal and stable over time. We have undertaken a microsatellite marker analysis of T. b. rhodesiense isolates in a relatively new active HAT focus in Uganda (Kaberamaido-Dokolo-Amolatar) over a six-year period (2006–2012). We amplified six microsatellite markers by PCR directly from blood spotted FTA cards following whole genome amplification. The majority of loci demonstrated an excess of heterozygosity (Ho > He, FIS < 0). We identified 26 unique genotypes among the 57 isolates, accounting for 45.6 % genotypic polymorphism. The presence of a high proportion of samples with repeated genotypes (54.4 %, 31/57), disagreement with Hardy-Weinberg equilibrium, and significant linkage disequilibrium between loci pairs, provide evidence that T. b. rhodesiense isolates from this focus are clonal. Our results show low values of FST’ (0–0.115) indicating negligible genetic differentiation across temporal isolates. Furthermore, predominant genotypes isolated in 2006 were still detectable in 2012. Our findings confirm the notion that endemicity is maintained by stable genotypes rather than an influx of new genotypes. Our results have considerable importance in understanding and tracking the spread of sleeping sickness with significant implication to disease control.
Keywords: Population; Genetic structure; Trypanosoma brucei rhodesiense